Potential of Bioactive Components in Tempe for the Treatment of Obesity - Astawan, Made; Mardhiyyah, Yunita Siti; Wijaya, Christofora Hanny (Jurnal Gizi dan Pangan, 2018)
Obesity has become a global health issue and is one of the factors that trigger degenerative diseases. The correct food consumption management could be a solution for treating obesity. Soybean is a food that is rich in bioactive components and has antiobesity properties through various mechanisms. In Indonesia, nearly 60% of the soybeans are consumed in the form of tempe. The process of fermenting soybeans into tempe causes a bioconversion of nutrients and bioactive components, improving the active physiological abilities. The bioactive components that play a role in the treatment of obesity are isoflavones, proteins, and peptides. These bioactive components help in reducing body weight, lowering the body fat ratio and improve lipid profile. Thus, optimation and popularization of tempe as a functional food in the daily menu supported with correct tempe processing could be a solution in treating obesity.